Managing virtual libraries of the future : the knowledge management perspective / Shaharom TM Sulaiman and Azree Ahmad - Sulaiman, Shaharom TM; Ahmad, Azree (Faculty of Information Management, 2005)
Two information science emerging emerging field of studies in the late 90 's, that is digital libraries and knowledge management were discussed. Thoughts and basic principles studied by pioneers in knowledge management were put forward. Knowledge management showed enormous concern and could be viewed from the perspective of information and library science, business management, and computer studies. Opportunities provided by digital libraries were linked within the knowledge management's values and advantages.